Morphometric Analysis of Coracoid Process in Adult Human Scapula in Eastern Odisha Population - Saurjya Ranjan Das1, Sreepreeti Champatyray2 , Gyanaranjan Nayak3, Sitansu Kumar Panda3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Coracoid process is a bird’s beak like projection which arises superolaterally from the upperborder of the head. It plays an important role in shoulder function. The aim of our study is to measure thedimensions of the coracoid process of the scapula.Method: The study was performed on 104 specimens of human scapula of unknown sex obtained from theDepartment of Anatomy of Institute of Medical Sciences & SUM hospital. The dimensions recorded werebreath, length, height,thickness and types of coraco-glenoid space by using digital vernier calipers. Theseparameters were compared on both the sides.Results: The most predominant coraco-glenoid space was found to be the round bracket (Type I).Statistically insignificant difference was noted in all four parameters between right and left. Though all thefour parameters have higher values on right side in comparison to left side but the difference was statisticallyinsignificant. The results are as such length of coracoid- 39.91±3.16 mm; width of coracoid- 14.00±2.03mm; tip thickness of coracoid- 8.32±1.87 mm; height of base coracoid- 22.87±3.55 mm; width of base ofcoracoid- 10.50 ±2.64 mm;Conclusions: The study of variation of dimensions of coracoid process provides valuable informationregarding the role of these parameters in etiology of subcoracoid impingement syndrome which will helpthe radiologist and orthopedic surgeons for diagnosing various pathologies and plan for surgical procedureon coracoid process.